Penerapan Fungsi Mid Dan Find pada Pembersihan Data Alamat - Aristejo; Sigit Wijanarko; Subhiyanto; Aji Santoso (Jurnal Teknik Informatika, 2024)
Interacting with data is a common occurrence. However, it should be realized that the data received often requires refinement to make it easier to read and search. The data refinement process is called as data cleansing. For instance, inconsistency of address writing often occurs, such as street names and city names mixed in the same field. Hence, it is difficult to read and be processed further. Excel provides the MID and FIND functions. If these two functions are combined, they will help us separate the city name from the street name and also placing the city name in its own column.